2017
DOI: 10.2217/bmm-2017-0215
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Potential Prognosticators of Neurological Outcome in Out-Of-Hospital Cardiac Arrest Patients

Abstract: Out-of-hospital cardiac arrest survival rates have increased due to advancement in resuscitative measures, yet approximately 90% of survivors ultimately die or have severe neurologic dysfunction caused by ischemic injury. Currently, there are few early prognostic indicators of which patients have possibility of meaningful recovery. This leads to uncertainty for families and clinicians, as well as aggressive, invasive and expensive treatments despite medical futility. Several biomarkers investigated in traumati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…Novel prognostic biomarkers include neurofilament light chain (NFL), tau protein and microRNAs. [31][32][33] Recently in a large sub-study of the TTM trial, serum NFL was shown to have significantly greater performance than the other biomarkers (ie, NSE, S-100 and tau) and its level at 24 hours after CA was even a robust indicator of long-term poor neurologic outcome. 33 No single test can accurately predict the prognosis of patients following CA.…”
Section: Discussionmentioning
confidence: 99%
“…Novel prognostic biomarkers include neurofilament light chain (NFL), tau protein and microRNAs. [31][32][33] Recently in a large sub-study of the TTM trial, serum NFL was shown to have significantly greater performance than the other biomarkers (ie, NSE, S-100 and tau) and its level at 24 hours after CA was even a robust indicator of long-term poor neurologic outcome. 33 No single test can accurately predict the prognosis of patients following CA.…”
Section: Discussionmentioning
confidence: 99%